Discomfort relief after paracetamol administration in febrile children admitted to a third level paediatric emergency department - Chiappini, Elena; Bestetti, Matilde; Masi, Stefano; Paba, Teresa; Venturini, Elisabetta; Galli, Luisa (Frontiers in Pediatrics, 2023)
Background international guidelines recommend treating fever in children not at a predefined body temperature limit but based on the presence of discomfort. However few studies evaluated discomfort relief after administration of antipyretics in children. Methods Between 1st January and 30th September 2021 a single-center prospective observational study was performed in febrile children consecutively admitted to a pediatric emergency department and treated with paracetamol orally. For each child, body temperature, presence and severity of discomfort, defined using a previously published semiquantitative likert scale, were evaluated at baseline and 60 min after administration of paracetamol, and differences were analyzed. Results 172 children (males: 91/172; 52.9%; median age: 41.7 months) were included. Significant reductions in body temperature (median body temperature at T0: 38.9 °C; IQR: 38.3–39.4, median body temperature at T60: 36.9 °C; IQR: 36.4–37.5; P < 0.0001), and in the level of discomfort (proportion of children with severe discomfort at T0: 85% and at T60:14%; P < 0.0001) were observed. Severe discomfort at T60 persisted in a minority of children (24/172; 14%) and it was not related to body temperature values. Conclusions paracetamol in febrile children is associated not only with significantly reduction in body temperature but also with discomfort relief.